Meningkatkan Hasil Belajar Siswa dengan Bantuan Visualisasi Video dan Gambar Menggunakan Model Pembelajaran Problem Based Learning di SMP Swasta Cinta Rakyat 1 Pematangsiantar - Hermanto Simamora (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Education plays an important role in shaping students' character and competencies, especially in the era of globalization which requires critical and creative thinking skills. At Cinta Rakyat 1 Junior High School, Pematangsiantar City, especially class IX-A, student learning outcomes in several subjects still need to be improved. Initial observations show that many students have difficulty understanding abstract concepts conveyed verbally without the support of visual media, as well as a decrease in learning motivation due to monotonous conventional teaching methods. The use of visual media in the form of videos and images is expected to help students understand complex concepts more easily and improve memory, thereby improving learning evaluation results and increasing active student involvement. This research focuses on improving student learning outcomes in Catholic Religious Education and Character Education subjects in class IX-A by using visual media as a tool in the learning process. The research subjects were all 32 students in class IX-A. Improved learning outcomes are measured through formative assessments in the form of written tests and observations of student activity and involvement during learning. The research problem formulation includes the effectiveness of using visual media in improving learning outcomes, motivation, student involvement, and understanding of abstract concepts. The research results are expected to make a significant contribution in improving the quality of learning through a visual approach that is relevant to student needs.